Padrão de especialização comercial e crescimento econômico : uma análise sobre o Brasil no contexto da fragmentação da produção e das cadeias globais de valor - Hermida, Camila do Carmo (2016)
Globalization and technological changes that has happened since the 80s have brought remarkable changes in the industrial and commercial paradigm, which are expressed mainly in the international fragmentation of production and in the formation of Global Value Chains (GVC). This thesis sought to understand such phenomena and discuss new relevant variables in this context for a more accurate analysis of the current trade patterns not addressed by the seminal economic theories that relate trade and economic growth. It sought to evaluate how the trade specialization pattern of Brazil evolved compared to other economies (China, India, Russia, United States, Japan and selected Latin American economies) in the light of these phenomena from 1995 to 2011. Therefore, we have used the methodology of gross exports decomposition in value added measures, developed by Koopman et al. (2014), and indicators estimated from data of two global matrices I-O: a WIOT (2013) and the TiVA (2015). It was also tested two hypotheses regarding the role of these phenomena as determinants of economic growth in recent years: 1º) fragmentation and participation in GVC ensure higher growth rates for countries; 2º) the place (stage) in which the country finds itself in GVC associated with sectoral technological aspects is also important for economic growth. For this, we used dynamic panel models (Difference GMM and System GMM) for a sample of 40 countries from 2003 to 2011. The studies carried out on Brazil show that the country is no longer on the margins of these phenomena, because it shows increasing rates of participation in GVC, including in sectors considered most strategic for fragmentation. However, there is not a standard convergence of trade specialization of the country to those presented by developed countries or movements earned by China and Mexico in terms of their position and profile of participating in GVC. Another important result obtained by the thesis is the identification of these phenomena are in fact new variables relevant for economic growth, because it shows empirical evidences to support the hypothesis 1 and, partially, the hypothesis 2. A joint analysis of the estimated econometric results with the results of the descriptive analysis of the Brazilian economy, it leads us to conclude that the trade specialization pattern of the country in the context of the new trade setups is presented unfavorably to its growth strategy.